A Study of Literatures and Ideas of Rabindranath Tagore: A Great Indian Writer: Exploring the Literary and Cultural Contributions of Rabindranath Tagore (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Rabindranath Tagore had early success as a writer in his native Bengal. With his translations of some of his poems he became rapidly known in the West. He was also a cultural reformer who modified Bengali art by rebuffing the strictures that confined it within the sphere of classical Indian forms. Though he was a polymath, his literary works alone are enough to place him in the elite list of all-time greats. Even today, Rabindranath Tagore is often remembered for his poetic songs, which are both spiritual and mercurial. Being a natural poet, his poetic outpourings in Bengali began to rejuvenate and recreate Bengali literature. In his late twenties he was entrusted with the responsibility of looking after the family estates in North Bengal. There he came into contact with the daily life of the village folk. He started his village re-construction program there. Tagore was a great humanist, painter, patriot, poet, playwright, novelist, story-teller, philosopher, and educationist. As a cultural ambassador of India he gave voice to the country and became an instrument in spreading the knowledge of Indian culture around the world.